Bifunctional Carbon‐Dot‐WS2 Nanorods for Photothermal Therapy and Cell Imaging. Issue 4 (14th December 2016) - Nandi, Sukhendu; Bhunia, Susanta Kumar; Zeiri, Leila; Pour, Maayan; Nachman, Iftach; Raichman, Daniel; Lellouche, Jean‐Paul Moshe; Jelinek, Raz
Abstract: Multifunctional nanoparticles have attracted significant interest as biomedical vehicles, combining diagnostic, imaging, and therapeutic properties. We describe herein the construction of new nanoparticle conjugates comprising WS2 nanorods (NRs) coupled to fluorescent carbon dots (C‐dots). We show that the WS2 ‐C‐dot hybrids integrate the unique physical properties of the two species, specifically the photothermal activity of the WS2 NRs upon irradiation with near‐infrared (NIR) light and the excitation‐dependent luminescence emission of the C‐dots. The WS2 ‐C‐dot NRs have been shown to be non‐cytotoxic and have been successfully employed for multicolour cell imaging and targeted cell killing under NIR irradiation, pointing to their potential utilization as effective therapeutic vehicles. Abstract : Hybrid nanorods : New composite WS2 ‐carbon‐dot nanorods have been designed and synthesized. Their potential applications for cell imaging and photothermal therapy have been demonstrated (see figure).